2023
DOI: 10.1007/s10123-022-00317-x
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus in cow milk and milk products in Ambo and Bako towns, Oromia, Ethiopia: prevalence, associated risk factors, hygienic quality, and antibiogram

Abstract: BackgroundStaphylococcus aureus is one of the foodborne gram-positive bacterial pathogens that cause staphylococcal food poisoning worldwide and can contaminate foods of animal origin. The current study was conducted in Ambo and Bako towns, Ethiopia to estimate the prevalence, associated risk factors, hygienic quality, and antibiogram of Staphylococcus aureus (S. aureus) in cow's raw milk and milk products. ResultsThe overall prevalence of S. aureus from milk and milk products was 15.6% (94/601) with the highe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
3
5
1
Order By: Relevance
“…Our findings are consistent with previous studies documenting tetracycline resistance rates ranging from 32.4 to 47.8% in milk and milk products in Ethiopia [ 11 , 53 , 70 ], Algeria [ 2 ], Egypt [ 46 ], and China [ 5 ]. Contrary to our results, earlier studies in Ethiopia [ 22 , 48 ], Iran [ 9 ], and Uganda [ 54 ] reported a high proportion of tetracycline-resistant S. aureus strains, ranging from 56.1 to 83.33%. The variation in tetracycline resistance levels between the current study and previous research likely arise from differences in antibiotic usage practices.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Our findings are consistent with previous studies documenting tetracycline resistance rates ranging from 32.4 to 47.8% in milk and milk products in Ethiopia [ 11 , 53 , 70 ], Algeria [ 2 ], Egypt [ 46 ], and China [ 5 ]. Contrary to our results, earlier studies in Ethiopia [ 22 , 48 ], Iran [ 9 ], and Uganda [ 54 ] reported a high proportion of tetracycline-resistant S. aureus strains, ranging from 56.1 to 83.33%. The variation in tetracycline resistance levels between the current study and previous research likely arise from differences in antibiotic usage practices.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar resistance rates for penicillin, ranging from 69.9 to 98.5%, have been documented in various regions of Ethiopia [ 22 , 70 , 71 ], while rates of 76–91.3% have been reported in Algeria [ 2 ], Egypt [ 46 ], and China [ 5 ]. Consistent with our findings, previous studies have reported proportions of ampicillin-resistant S. aureus ranging from 70.9 to 98.5% in different regions of Ethiopia [ 11 , 48 , 53 , 71 ], and rates ranging from 72.94 to 90.3% in Egypt [ 46 ], Turkey [ 56 ], Uganda [ 72 ], and China [ 5 ]. Supporting these observations, a global meta-analysis reported similarly high resistance levels, with penicillin resistance at 73.85% and ampicillin resistance at 59.63% [ 59 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations